Kedudukan Siyasah Dusturiyyah Studi Kasus Politisasi Pemilu 2024 Analisis Peradilan Hukum Islam - Jaidi, Muhammad; Hasan , Ahmadi; Umar , Masyithah; Khasyi’in, Nuril (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract Analysis of the position of siyasah dusturiyyah (constitutional politics) in the context of the politicization of the 2024 Elections in Indonesia and from the perspective of Islamic judicial law. The research employs a qualitative approach with descriptive-analytical methods, examining relevant literature and secondary data to reveal how siyasah dusturiyyah is applied in the political and legal processes of elections. The findings indicate that siyasah dusturiyyah is a fundamental element in the formation of state law, encompassing legislation, government administration, and the enforcement of fair and transparent laws in accordance with Sharia principles. In the context of the 2024 Elections, integrity and neutrality are highlighted as key factors in ensuring fairness and representativeness in governance. The Constitutional Court (MK) plays a strategic role in resolving electoral disputes, upholding the rule of law, and ensuring the electoral process is fair. The research asserts that the collaboration between law and politics through the siyasah dusturiyyah framework can create a stable, just, and accountable governance system. By applying Sharia principles in political and legal processes, the government can reflect Islamic teachings while fulfilling the aspirations of society as a whole. Integrity and transparency in elections are identified as imperative to achieve a representative and just government. Keywords: Siyasah Dusturiyyah, Election Politicization, 2024 Elections, Islamic Law, Judicial Analysis, Position. Abstrak Analisis kedudukan siyasah dusturiyyah (politik perundang-undangan) dalam konteks politisasi Pemilu 2024 di Indonesia dan dari perspektif peradilan hukum Islam. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif-analitis, mengkaji literatur dan data sekunder yang relevan untuk mengungkap bagaimana siyasah dusturiyyah diterapkan dalam proses politik dan hukum pemilu. Temuan penelitian menunjukkan bahwa siyasah dusturiyyah merupakan elemen fundamental dalam pembentukan hukum negara, mencakup pembuatan undang-undang, administrasi pemerintahan, dan penegakan hukum yang adil dan transparan sesuai dengan prinsip-prinsip syariah. Dalam konteks Pemilu 2024, integritas dan netralitas dinyatakan sebagai faktor kunci untuk menjamin keadilan dan representativitas pemerintahan. Mahkamah Konstitusi (MK) berperan strategis dalam menyelesaikan sengketa pemilu, menegakkan aturan hukum, dan memastikan proses pemilu berjalan dengan adil. Penelitian ini menegaskan bahwa kolaborasi antara hukum dan politik melalui kerangka siyasah dusturiyyah dapat menciptakan sistem pemerintahan yang stabil, adil, dan akuntabel. Dengan menerapkan prinsip-prinsip syariah dalam proses politik dan hukum, pemerintah dapat mencerminkan ajaran Islam sekaligus memenuhi aspirasi masyarakat secara menyeluruh. Integritas dan transparansi dalam pemilu diidentifikasi sebagai keharusan untuk mencapai pemerintahan yang representatif dan berkeadilan. Kata Kunci: Siyasah Dusturiyyah, Politisasi Pemilu, Pemilu 2024, Hukum Islam, Analisis Peradilan, Kedudukan.